High-temperature oxidation and erosion of HVOF sprayed NiCrSiB/Al2O3 and NiCrSiB/WCCo coatings - Ayyappan Susila Praveen (Elsevier, 2022)
Material deterioration due to erosion and oxidation in high-temperature environments is a major cause of wear in power plants, aircraft engines and petrochemical industries. NiCrSiB based surface coatings using thermal spray techniques such as High-Velocity Oxy-Fuel (HVOF) offer a cost-effective route to improve the tribological properties for a range of substrate materials. The study investigates the high-temperature oxidation and erosion resistance of HVOF coated NiCrSiB reinforced with Al2O3 and WCCo on SS304 stainless steel substrate. The oxidation kinetics and erosion responses of the coatings at 750 °C were evaluated for a period of 160 hrs and the coating microstructure, morphology and chemical compositions characterised. A total of three coating compositions were studied namely: NiCrSiB/Al2O3, NiCrSiB/n-Al2O3 and NiCrSiB/WCCo where the results indicate a superior oxidation and erosion resistance in all cases in comparison to uncoated SS304. However, it was found that the NiCrSiB reinforced with micro-structured Al2O3 outperformed all the other coatings in terms of oxidation resistance. When it comes to erosion resistance, NiCrSiB/WCCo was found to demonstrate the highest performance.